The involvement of microRNAs in neurodegenerative diseases - Maciotta Rolandin, Simona; Meregalli, Mirella; Torrente, Yvan (Frontiers in Cellular Neuroscience, 2013)
Neurodegenerative diseases (NDDs) originate from loss of neurons in the central nervous system and are severely debilitating. They are worldwide spread and their incidence increases with age so that they are supposed to become more common due to extended life expectancy. Since no cure is available they have become a major challenge to neurobiology. The increasing relevance of microRNAs (miRNAs) in biology has prompt the scientific society to investigate on their possible involvement in neurodegeneration with the aim to find new therapeutic targets. Indeed the idea of using miRNAs as therapeutic targets is nowadays not far from realization but important issues need to be addressed before moving towards the clinics. With the present review we aim to resume what have been so far disclose on the involvement of miRNAs in NDDs pathogenesis. Furthermore, their expression levels in peripheral tissues of patients affected by NDDs will be here reported in order to evaluate their application as biomarker of disease. Finally the discrepancy, innovation and effectiveness of data collected will be elucidated and discussed.